Potato starch modification using the ozone technology - Silva, Nanci Castanha da (2017)
Starch modification is a widely employed and important technique, allowing to obtain ingredients with different characteristics, expanding the range of applications of starches and bringing competitive advantages for different industries. Despite the production of toxic residues, and despite the increasing concern about environmental issues, the use of chemical agents in starch modification by oxidation is still very popular. Ozone can be a solution to change it, since is a very powerful oxidising agent that can be quickly decomposed into oxygen, whose residues meet the global demand for sustainability. Therefore, it can be a safer alternative for both consumers and environment. In this work the use of ozone in aqueous solution as a starch modification method was evaluated. The effects of the different ozonation times on the structure and properties of the potato starch were investigated. With increasing the ozonation time, it was observed an increase in the carbonyl, carboxyl and reducing sugar contents, as well as a decrease in the pH, apparent amylose content and molecular size, demonstrating that the potato starch processed with ozone was modified in its molecular level. Further, X-ray diffraction analysis showed no significant changes in the relative crystallinity of the granules, while in the microscopy analysis it was observed some alterations in the granules morphology. All these changes directly affected the modified starch properties, resulting in significant differences in the pasting properties, gel texture and paste clarity. The obtained results are promising, since they can prove the effectiveness of using ozone, a still little explored and sustainable method, as an efficient oxidizing agent for starch modification.